If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.5x + -1(0.5 + -1x) = 0 1.5x + (0.5 * -1 + -1x * -1) = 0 1.5x + (-0.5 + 1x) = 0 Reorder the terms: -0.5 + 1.5x + 1x = 0 Combine like terms: 1.5x + 1x = 2.5x -0.5 + 2.5x = 0 Solving -0.5 + 2.5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + 2.5x = 0 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + 2.5x = 0 + 0.5 2.5x = 0 + 0.5 Combine like terms: 0 + 0.5 = 0.5 2.5x = 0.5 Divide each side by '2.5'. x = 0.2 Simplifying x = 0.2
| 7x+9=0.5(8x-12) | | 4x-(9x+5)=9x-19 | | 1.75x-(.75-x)=0 | | -2x(x-3)=4x+6 | | .2(40x+20)-19=-.5(14x-10) | | 3x(x+3)-6=5x-5 | | 5x-x+x=24 | | 5x+3=10x-9 | | g(x)=4(-5)-5 | | 8x-10=2(4x-7) | | 9(x+8)=5(x-(4-x)) | | (2y-(3y-4)+5y-6)+10y=(12y-12)+36 | | 4x^2-65x+64=0 | | 6x+20=8x+6y | | 6a+5a+2a-6= | | (x/y)(100)=-18 | | (x/Y)*100=-18 | | x^5+4x^4-3x^2+x-6=0 | | (3x^2)-14x+16=0 | | Y=ln(5x^2-9x+2) | | (-3x+5y)-(-2x+4y)= | | 23-5x=14+4 | | 6y-22y= | | f(x)=(0.93) | | (10x-5)/5=15 | | -7x-2=49 | | y=3lnx/2lnx | | 5-8z=-11 | | 180-x=165-2(90-x) | | y=1-6x^2 | | 5x+12=-3x+36 | | 10-3x=2.5x |